1998
DOI: 10.1074/jbc.273.5.2947
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection of Bacteriophage φ29 Prohead RNA Aptamers for Prohead Binding

Abstract: Prohead RNA (pRNA) of the Bacillus subtilis bacteriophage 29 is needed for in vitro packaging of DNA-gene product 3 (DNA-gp3). Residues 22-84 of the 174-base pRNA bind the portal vertex of the prohead, the site of DNA packaging. To define the nucleotides of pRNA needed for prohead binding and DNA-gp3 packaging and to seek biologically active variants of pRNA, segments of pRNA were randomized to obtain vast repertoires of RNA molecules. RNA aptamers, ligands best suited for prohead binding, were obtained by mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 14 publications
1
6
2
Order By: Relevance
“…In addition, the 2D 1 H- 1 H NOESY spectra of the 19-mer/35 -uucg heterodimer are the same as those of the 19-mer/35-mer heterodimer, except for the signals derived from residues within the UUCG tetraloop (data not shown). Whereas previous mutagenesis studies have shown that the E-loop is important for the DNA packaging activity ( 17 , 43 ) and chemical modification show that it becomes protected during oligomerization ( 45 ), our current studies suggest that the E-loop is not directly involved in the intermolecular interaction of pRNA in solution.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In addition, the 2D 1 H- 1 H NOESY spectra of the 19-mer/35 -uucg heterodimer are the same as those of the 19-mer/35-mer heterodimer, except for the signals derived from residues within the UUCG tetraloop (data not shown). Whereas previous mutagenesis studies have shown that the E-loop is important for the DNA packaging activity ( 17 , 43 ) and chemical modification show that it becomes protected during oligomerization ( 45 ), our current studies suggest that the E-loop is not directly involved in the intermolecular interaction of pRNA in solution.…”
Section: Discussioncontrasting
confidence: 86%
“…The result of this modified HNN-COSY experiment was also negative as we did not observe any signal indicating intermolecular A–U base pairing using the U-labeled 19-mer/A-labeled 35 -uucg heterodimer (data not shown). These results indicated that only two G–C base pairs are stably formed between the D-loop and the CE-loop, in contrast to the hypothesis that four base pairs are formed between these loops ( 5 , 6 , 43 , 44 ).…”
Section: Resultscontrasting
confidence: 66%
“…75 98-101 SELEX allows screening for co-variation of several nucleotides and can be used to reveal noncanonical interaction which is difficult to prove by classic genetic and biochemical approaches. 75 98-101 For example, SELEX has been used to select pRNA sequences that bind procapsids 102 and proved that pRNA can bind ATP. …”
Section: Selexmentioning
confidence: 99%
“…If the protein does not contain such a tag, separation of bound and unbound DNA molecules can be carried out by using nitrocellulose filters (Millipore HWAP), which will retain the protein−DNA library complex while letting the unbound DNA pass through. Other methods for separating ligands without tags include capillary electrophoresis (12), gel electrophoresis (13), sedimentation centrifugation (14), and flow cytometry (15 3. During PCR amplification of selected DNA, it is important not to over-amplify the sequences.…”
Section: Notesmentioning
confidence: 99%